2016
DOI: 10.1007/s10571-015-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Cerebral Blood Flow as a Biomarker of Preclinical Alzheimer’s Disease

Abstract: There is accumulating evidence suggesting that changes in brain perfusion are present long before the clinical symptoms of Alzheimer’s disease (AD), perhaps even before amyloid-β accumulation or brain atrophy. This evidence, consistent with the vascular hypothesis of AD, implicates cerebral blood flow (CBF) in the pathogenesis of AD and suggests its utility as a biomarker of preclinical AD. The extended preclinical phase of AD holds particular significance for disease-modification, as treatment would likely be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(158 citation statements)
references
References 117 publications
(157 reference statements)
7
143
0
1
Order By: Relevance
“…Furthermore, our sample of cognitively normal older adults demonstrated an overall positive association between memory function and CBF that was modified by SCD, such that those presenting without SCD showed positive associations between memory functions and CBF within frontal, temporal, and parietal regions, whereas those presenting with SCD showed negative associations between memory function and CBF within frontal, temporal, and parietal regions. Our results showing that those with SCD demonstrate both higher and lower regional CBF, compared to those without SCD, are consistent with other SCD-related perfusion studies, further supporting the notion that regionally specific perfusion differences exist between these groups in areas that have been implicated in normal aging and AD-risk (Dai et al, 2009; Hays et al, 2016; Meltzer et al, 2000). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, our sample of cognitively normal older adults demonstrated an overall positive association between memory function and CBF that was modified by SCD, such that those presenting without SCD showed positive associations between memory functions and CBF within frontal, temporal, and parietal regions, whereas those presenting with SCD showed negative associations between memory function and CBF within frontal, temporal, and parietal regions. Our results showing that those with SCD demonstrate both higher and lower regional CBF, compared to those without SCD, are consistent with other SCD-related perfusion studies, further supporting the notion that regionally specific perfusion differences exist between these groups in areas that have been implicated in normal aging and AD-risk (Dai et al, 2009; Hays et al, 2016; Meltzer et al, 2000). …”
Section: Discussionsupporting
confidence: 91%
“…Research suggests that dysfunction within the vascular neural network can lead to neuronal injury and degeneration (Lo & Rosenberg, 2009; Zlokovic, 2010). Cerebral blood flow (CBF), or the rate of delivery of arterial blood to the capillary bed of a particular mass of tissue, is a functional measure of the vascular neural network and has been implicated in both normal aging and Alzheimer’s disease (AD)-related cognitive decline (Bertsch et al, 2009; Hays, Zlatar, & Wierenga, 2016; Heo et al, 2010). CBF has demonstrated reliable correlations with cognition across the lifespan in both normal and pathologic aging (Bangen et al, 2012; Bertsch et al, 2009; Okonkwo et al, 2014; Wierenga et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathways by which CBVD may influence or interact with the development or progression of ADNP likely involve cerebral blood flow dysregulation. CBVD can lead to cerebral hypoperfusion that could result in degradation of the neurovascular unit and subsequent deposition of beta-amyloid and tau, eventually leading to dementia (this vascular pathway has been the focus of several literature reviews [7072]). The relationship between cerebral blood flow and ADNP remains inconclusive, given a recent study that found no association between cerebral blood flow and cortical uptake of amyloid (flutemetamol) or tau (AV-1451) tracers on PET imaging in 11 middle-aged to elderly patients with unilateral occlusion of precerebral arteries [73].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood flow (CBF), or the rate of delivery of arterial blood to the capillary bed in a volume of tissue, is an indirect measure of neural function that can reliably distinguish between normal controls and those with AD, identify those at risk for MCI and AD, and predict conversion to MCI and AD (Hays, Zlatar, & Wierenga, 2016; Wierenga, Hays, & Zlatar, 2014). While some evidence suggests that AD-risk is associated with lower CBF, particularly in medial temporal lobe (MTL) regions, other studies support higher CBF among those at risk (Hays et al, 2016). These conflicting results are likely due to differences in sample characteristics (e.g., operational definitions of MCI or normal control, APOE genotype, age), or methodological differences (e.g., imaging modality limitations, statistical or experimental control of confounding variables).…”
Section: Introductionmentioning
confidence: 99%